2013
DOI: 10.5935/1808-8694.20130075
|View full text |Cite
|
Sign up to set email alerts
|

Does Epstein-Barr virus infection have an influence on the development of laryngeal carcinoma? Detection of EBV by Real-Time Polymerase Chain Reaction in tumour tissues of patients with laryngeal carcinoma

Abstract: Our results suggest that, although EBV is present in some of the squamous cell laryngeal carcinomas, its presence has no effect on the pathogenesis of laryngeal carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 23 publications
3
22
1
1
Order By: Relevance
“…Tobacco smoking and alcohol consumption are the largest risk factors for LSCCs, and create an imbalance between cases and controls, which we have adjusted for in our analyses. Since we only used the laryngeal cases to check whether antibodies distinguish between NPCs and non‐NPCs, they display a suitable control group, as LSCCs are not known to be associated with EBV infection 27 . LSCC is rarely (<5%) 18 associated with HPV infection, however, we have not calculated risk estimates for HPV serology that could have been affected by HPV‐positive LSCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco smoking and alcohol consumption are the largest risk factors for LSCCs, and create an imbalance between cases and controls, which we have adjusted for in our analyses. Since we only used the laryngeal cases to check whether antibodies distinguish between NPCs and non‐NPCs, they display a suitable control group, as LSCCs are not known to be associated with EBV infection 27 . LSCC is rarely (<5%) 18 associated with HPV infection, however, we have not calculated risk estimates for HPV serology that could have been affected by HPV‐positive LSCCs.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that EBV infection is associated with a reduction of the number of CD4 + Tlymphocytes in patients with EBV-related cancer (20). Despite the involvement of EBV infection in the development of cancer having been extensively studied (5,8,9,(21)(22)(23)(24)(25)(26)(27), reports analyzing the initial phase of immune response and lymphocyte activation affected by viral infection are rare. During primary EBV infection, antibodies to VCA IgM are generated and persist from weeks to months.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic Epstein-Barr virus (EBV) infection is regarded as an important risk factor for the occurrence of tongue and oropharyngeal cancer (5,6) and is etiologically linked with undifferentiated nasopharyngeal carcinoma (7). EBV DNA was identified in 60% of patients with laryngeal carcinoma (8) EBV is widespread in the human population, with seropositivity in IgG class antibodies reaching more than 95% suggesting past infection (9). Primary EBV infection is manifested as acute infectious mononucleosis, however, it more often occurs as asymptomatic disease (10).…”
mentioning
confidence: 99%
“…Genotypes 16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, and 59 are known as a high-risk HPV (HR-HPV) since they are directly associated with the development of cancer, including cervical, penile, anal, and throat ( Fakhry & Gillison, 2006 ; Omland et al, 2014 ; Lajer & Von Buchwald, 2010 ). Several epidemiologic and biological studies have implicated the HR-HPV infection, mainly genotypes 16 and 18, as a potential etiological factor for the development of tumors in the upper aerodigestive tract but other well-defined oncogenic viruses, such as Epstein-Barr virus (EBV) or Merkel cell polyomavirus (MCPV), might have a role in the pathogenesis of this type of tumors ( Gama et al, 2016 ; Sturgis, Wei & Spitz, 2004 ; De Oliveira et al, 2006 ) EBV belongs to the group of herpesviruses and its initial transmission is via the oropharynx, where it has been associated to the etiopathogenesis of an increasing number of cancers; however, the mechanism of the immunopathogenesis of the infection caused by this virus has not yet been elucidated ( Hutt-Fletcher, 2017 ; Goldenberg et al, 2004 ; Muderris et al, 2013 ). Polyomaviruses are oncogenic viruses closely related to HPV that have the capacity to transform cellular morphology.…”
Section: Introductionmentioning
confidence: 99%